1997
DOI: 10.1523/jneurosci.17-06-01891.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Activity of Group-II Metabotropic Glutamate Receptors Requires New Protein Synthesis and Involves a Glial–Neuronal Signaling

Abstract: The group-II metabotropic glutamate (mGlu) receptor agonists (2S,1′R,2′R,3′R)-2-(2,3-dicarboxycyclopropyl)glycine (DCG-IV), S-4-carboxy-3-hydroxyphenylglycine (4C3HPG), and (2S,1′S,2′S)-2-(carboxycyclopropyl)glycine (L-CCG-I) protected mouse cortical neurons grown in mixed cultures against excitotoxic degeneration induced by a 10 min pulse with NMDA. Protection was observed not only when agonists were added in combination with NMDA but also when they were transiently applied to cultures 6–20 hr before the NMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 31 publications
4
89
0
2
Order By: Relevance
“…This offers the advantage to examine the respective contribution of astrocytic and neuronal mGlu2 and mGlu3 receptors to processes of neurodegeneration/neuroprotection. Neuroprotection by mGlu2/3 receptor agonists in mixed cortical cultures involves a mechanism of glial-neuronal interaction mediated by the production of transforming growth factor-␤ (Bruno et al, 1997(Bruno et al, , 1998bD'Onofrio et al, 2001). This mechanism was dem- onstrated by transferring the medium collected from astrocyte cultures treated with mGlu2/3 receptor agonists to recipient mixed cultures challenged with NMDA (Bruno et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This offers the advantage to examine the respective contribution of astrocytic and neuronal mGlu2 and mGlu3 receptors to processes of neurodegeneration/neuroprotection. Neuroprotection by mGlu2/3 receptor agonists in mixed cortical cultures involves a mechanism of glial-neuronal interaction mediated by the production of transforming growth factor-␤ (Bruno et al, 1997(Bruno et al, , 1998bD'Onofrio et al, 2001). This mechanism was dem- onstrated by transferring the medium collected from astrocyte cultures treated with mGlu2/3 receptor agonists to recipient mixed cultures challenged with NMDA (Bruno et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotection by mGlu2/3 receptor agonists in mixed cortical cultures involves a mechanism of glial-neuronal interaction mediated by the production of transforming growth factor-␤ (Bruno et al, 1997(Bruno et al, , 1998bD'Onofrio et al, 2001). This mechanism was dem- onstrated by transferring the medium collected from astrocyte cultures treated with mGlu2/3 receptor agonists to recipient mixed cultures challenged with NMDA (Bruno et al, 1997). Using the same strategy, we have now shown that the mechanism of glial/neuronal interaction is mediated by mGlu3 receptors and that activation of astrocytic mGlu3 receptors is responsible for neuroprotection induced by LY379268.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this neuroprotection is attributable to the inhibition of microglial toxin production or the stimulated release of additional neuroprotective substances remains to be determined. In astrocytes, mGlu receptor stimulation may lead to the release of neurotrophic factors, such as TGF-␤ (Bruno et al, 1997(Bruno et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%